Population genetic research in Hungary - Pap, Miklós (Acta Biologica Szegediensis, 2000)
In this short retrospective study, the author gives account of some aspects and the main results of human population genetical studies in Hungary. In the foreground of his interest is research taking as its basis the population as a genetic unit, which demonstrates the genetic structures of the populations, the geographic (and other) mechanisms of isolation, migration, the variability of genetic markers (blood group-, serum- and enzyme polymorphisms, deutan/protan anomaly), i.e., which are related to the problems of human micro-evolutional processes.